2005
DOI: 10.1002/clc.4960280608
|View full text |Cite
|
Sign up to set email alerts
|

Resting 12-lead electrocardiogram as a reliable predictor of functional recovery after recanalization of chronic total coronary occlusions

Abstract: SummaryBackground: A major goal of revascularization is the recovery of left ventricular (LV) function. Nuclear imaging techniques are widely used for detecting recovery of function with a good sensitivity, but only moderate specificity. Predictors of recovery in chronic total coronary occlusions (CTO) are not investigated.Hypothesis: The 12-lead-resting electrocardiogram (ECG) is a predictor of LV recovery after successful recanalization of CTO.Methods: Successful recanalization of CTO was performed in 127 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
0
15
0
3
Order By: Relevance
“…However, indirect data, such as absence of electrocardiographic Q waves or dyskinesia in the myocardium supplied by the occluded artery, support a viable myocardium or a possible recovery after recanalization. 36 Device setting was not done by an independent core laboratory and was left to the physician's discretion. However, all arrhythmic events were reviewed by the same electrophysiologist in a second stage and classified subsequently.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, indirect data, such as absence of electrocardiographic Q waves or dyskinesia in the myocardium supplied by the occluded artery, support a viable myocardium or a possible recovery after recanalization. 36 Device setting was not done by an independent core laboratory and was left to the physician's discretion. However, all arrhythmic events were reviewed by the same electrophysiologist in a second stage and classified subsequently.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The possibility of LV functional recovery with its beneficial effect on survival provides the rationale for the technically demanding attempt to recanalize a CTO. 35 The recovery of impaired systolic LV function after revascularization of a CTO appears not to depend on the quality of collateral function, 36 suggesting that collateral development does not depend on the presence of viable myocardium. Simultaneous assessment of regional LV function with the use of transthoracic tissue Doppler imaging and invasive collateral function has shown a statistically relevant association between systolic as well as diastolic LV function and collateral function in patients with CAD (Table).…”
Section: The Coronary Occlusion Model: Natural Versus Artificialmentioning
confidence: 99%
“…It has been reported that the absence of the Q-waves in a 12-lead ECG could predict the recovery of regional wall motion after the CTO PCI; nevertheless, only 22% answered that in such situation there is a need to prove the viability of akinetic region of myocardium [18]. The preferred test for viability assessment in our study was dobutamine stress echocardiography; we can presume that the availability and costs place this test above MRI.…”
Section: Discussionmentioning
confidence: 75%